Тhe Importance of Learning A Foreign Language in the System of Training Highly Qualified Personnel in the Field of Transport - Sheralieva Shakhnoza Irkinovna; Rasulova Zukhra Xakimberdievna; Xalikova Latofat Uktamovna (Zien Journals, 2022)
This article provides examples from practice the author's work when teaching a foreign language in the classroom, justifies the effectiveness of using various methods in the process studying a foreign language at a technical university, the article is devoted to the effective use of information and communication tools.
Keywords: A foreign language; technical university; student; teacher